Prototipe Kompresi Lossless Audio Codec Menggunakan Entropy Encoding - Soegandi, Andreas (ComTech: Computer, Mathematics and Engineering Applications, 2010)
The purpose of this study was to perform lossless compression on the uncompress audio file audio to minimize file size without reducing the quality. The application is developed using the entropy encoding compression method with rice coding technique. For the result, the compression ratio is good enough and easy to be developed because the algorithm is quite simple.